Sistem Pakar Untuk Mendiagnosa Penyakit Jantung Menggunakan Metode Dempster Shafer - Arjon Samuel Sitio (Journal Of Informatic Pelita Nusantara, 2018)
Expert system to diagnose heart disease at Medan Aviati Clinic. This study aims to create an Expert System application detects heart disease in Aviati Clinic by using Visual Basic programming language 2010. Data collection method used in research is observation and literature study. In making this application, the dempster shafer method is used to detect the risk of heart disease based on risk factors and symptoms that affect heart disease. From the results of research conducted, it can be concluded that the expert system detects heart disease in Aviati Clinic by using Visual Basic programming language 2010 can improve the performance of Aviati Clinic. Key Words: Expert System, Bone Disease, Dempster Shafer, Visual Basic 2010